Implementasi Sistem Monitoring Wadah Sampah Berbasis ESP32 untuk Efisiensi Pengelolaan di Bank Sampah KHALISA Cipedak - Irmayani; Fivit Marwita; Edi Widiono; S. Wahyu Dumadi; Edy Supriyadi; Ariman; M. Febriansyah; M. Fadhli Abdillah; Harlan Effendi; Iriandi Ilyas; Poedji Oetomo (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2026)
The Bank Sampah KHALISA RW 06 Cipedak is a community-based initiative in sustainable household waste management involving 200 households as active members. In its implementation, operational management still faces several challenges, including manual monitoring of waste bins, a limited number of collection staff, and the absence of a data-based system to support work efficiency. To address these issues, the Community Service team from the Electrical Engineering Department of ISTN designed and implemented an Internet of Things (IoT)-based waste bin monitoring system using an ESP32 microcontroller, an ultrasonic sensor, and a load cell. The system detects the fill level and weight of inorganic waste, displays information on an LCD, and sends real-time notifications to staff via the Telegram application. Trial results indicate that the device operates according to its design objectives. The implementation reduced collection delays by 90% and improved staff time efficiency by 80%, as waste collection is carried out based on the actual condition of the bins. In addition to its technical impact, the program also enhanced community participation and discipline in separating organic and inorganic waste. Although the reduction in operational costs has not yet been evaluated and the deployed devices remain limited in number, the system has proven effective in supporting more timely, structured, and data-driven waste management at the community level.